2012
DOI: 10.1002/jmv.23239
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous human immunodeficiency virus‐1 protein, tat, enhances replication of JC virus efficiently in neuroblastoma cell lines

Abstract: The high incidence of progressive multifocal leukoencephalopathy (PML) among individuals with acquired immunodeficiency syndrome (AIDS) is similar to the incidence of other immunocompromised diseases. The pathogenic JC virus (JCV) with rearranged regulatory regions (PML-type) causes PML, a demyelinating disease in the brains of immunocompromised patients. In a previous study, Tat protein, encoded by human immunodeficiency virus type 1 (HIV-1), markedly enhanced the expression of a reporter gene under control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Cell proliferation was determined by measuring mitochondrial succinate dehydrogenase activity using an MTT assay as described previously [Nukuzuma et al, 2012]. IMR‐32 cells were plated into 96‐well microtiter plates at a concentration of 7.1 × 10 4 cells/well in 100 µl medium and incubated in the absence or presence of 3‐AB at a final concentration of 20 mM for 5 days at 37°C in a CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation was determined by measuring mitochondrial succinate dehydrogenase activity using an MTT assay as described previously [Nukuzuma et al, 2012]. IMR‐32 cells were plated into 96‐well microtiter plates at a concentration of 7.1 × 10 4 cells/well in 100 µl medium and incubated in the absence or presence of 3‐AB at a final concentration of 20 mM for 5 days at 37°C in a CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…A DNA replication assay was carried out as described previously [Nukuzuma et al, 2012]. IMR‐32 cells were plated into poly‐ L ‐lysine‐coated 35‐mm dishes in 2 ml of DMEM containing with 10% FBS until they reached 70–80% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity was measured by an MTT assay, as previously described (13). IMR-32 and JCI cells were plated in 96-well microtiter plates at a concentration of 5.0 Â 10 4 (topotecan) or 2.5 Â 10 4 (b-lapachone) cells/ well/100 mL medium 24 hr prior to addition of various concentrations of topotecan or b-lapachone.…”
Section: Quantification Of Cell Proliferationmentioning
confidence: 99%
“…DNA replication assay using RT-PCR IMR-32 cells were cultured in 6-well plates containing 2 mL complete growth medium until 70-80% confluency had been reached. JCV DNA transfection was performed as previously described (13). Briefly, 1.0 mg viral DNA (M1-IMRb) excised from a recombinant plasmid with EcoRI was introduced into cells using FuGENE 6 transfection reagent (Roche), according to the manufacturer's instructions.…”
Section: Quantification Of Cell Proliferationmentioning
confidence: 99%
“…Recent studies have shown that HIV-1 viral proteins per se can act on oligodendrocytes and produce detrimental effects, which are independent of JCV [ 6 , 9 , 10 ]. HIV-1 viral proteins, including the envelope glycoprotein 120 (gp120), trans-activator of transcription (Tat), and negative regulatory factor (Nef), have been implicated in HIV-1-associated oligodendrocyte injury [ 9 , 11 , 12 , 13 , 14 ]. Among these viral proteins, Tat has consistently been detected in both infected and uninfected oligodendrocytes in the brains of AIDS patients [ 7 ], and exhibited a synergistic detrimental effect with JCV or with addictive drugs, such as morphine.…”
Section: Introductionmentioning
confidence: 99%